Effect of newly required American football headgear on thermoregulation during exercise in the heat - Langan, S. P.; Martin, D. G.; Thomas, L.; Good, A.; Funk, J. R.; Barker, R.; Deaton, S.; Guevel, S.; Crandall, J. R.; Sills, A.; Myers, B. S.; Arbogast, K. B.; et al. (Sports Engineering, 2025)
The Guardian Cap (GC) football helmet cover is designed to reduce head impact severity, but the influence on body temperature during exercise heat stress is unknown. We determined whether the GC NXT accentuates hyperthermia in a thermal manikin model and exercising humans (n = 12 males, 18-35 yrs, > 91 kg). The manikin assessed heat loss, heat absorption, thermal resistance, and evaporative resistance in four helmets with and without the GC NXT. The human study recorded rectal (Tr) and skin (Tsk) temperature, sweat rate, heart rate (HR), thermal sensation (ThS), rate of perceived exertion (RPE), and fatigue during five 90 min exercise trials in the heat (two helmet models each with and without white and black GC NXT`s). In the manikin, heat loss was lower by 2.35 W/m2 with all helmets when the GC NXT was worn (p = 0.0283). The effect of the GC NXT was small compared to the variation between helmet models (Hedges` g* = 0.13). Tr, Tsk, HR, and sweat rate were similar between trials in humans. Helmet temperatures were 5-10 °C lower with the GC NXT compared to the bare helmet (p < 0.001). ThS was lower with the white (p = 0.007) and black (p = 0.011) GC NXT, but RPE and fatigue were similar. Minor differences in heat loss and absorption were found in the manikin, but did not translate into altered thermoregulatory parameters in humans during intense exercise heat stress. The GC NXT did not significantly alter exertional hyperthermia, which can inform decision-making for product use.